The Role of Social Support on the Level of Loneliness among Migrant Students in Makassar - Anna Azizah; Muh. Daud (Psikoislamedia: Jurnal Psikologi, 2025)
The differences in life abroad present challenges for students in adapting to new cultures and environments, which often lead to feelings of alienation due to differences in socio-cultural norms and longing for loved ones. This condition can trigger negative emotions in the form of loneliness, which is influenced by social support. This study aims to examine the relationship between social support and loneliness in 349 first-year students from Makassar City aged 18-24 years living in boarding houses and originating from outside South Sulawesi. Using a quantitative approach with instruments in the form of a social support scale and a loneliness scale. Data analysis was carried out using the Kolmogorov-Smirnov normality test, ANOVA linearity test, and hypothesis testing using Pearson correlation. The results showed a significant negative relationship between social support and loneliness (r = -0.884, p < 0.05). This finding demonstrates the importance of family and friend support in preventing loneliness for students from traveling. Keywords: Loneliness, Migrant Students, Social Support